Nutrients in Matoa for Health and Exercise Performance: A Literature Study - Mandosir, Yohanis Manfred; Prasetyo, Yudik; Suhartini, Bernadeta; Kristanto, Budi (Formosa Journal of Science and Technology, 2025)
Matoa is an endemic plant in Indonesia that has great potential in the health sector. This study aims to examine the antioxidant potential of matoa through a narrative review approach. The literature search method was carried out on the Google Scholar and Research Gate databases with the keywords "matoa", "immunity", "health" and "exercise performance" limited to the last 10 years of publication. Of the 65 articles identified, 9 met the inclusion criteria for in-depth analysis. The results showed that matoa contained various bioactive compounds, especially phenolic groups that played a role in antioxidant, anti-inflammatory, cardiovascular and exercise performance. The use of matoa has been developed in various forms, ranging from health supplements to functional food products. This study also identifies the need for further research related to long-term safety evaluation and clinical validation to optimize the use of matoa in the health sector.